Macroeconomic linkages between selected east Asian economies and the US - Tan, E.C. (2010)
The paper will assess the extent of transmission of output shocks from the United States (US) to a number of East Asian economies. Quarterly data series spanning from the early 1990s would be mobilized for the purpose. The existing pattern of global economic recovery from the 2007 US subprime crisis would allude to the ability of East Asian economies to grow quite independently of the U.S. Indeed, certain quarters would even hail the region as a potential savior of the global economy. Greater intra‐regional trade and domestic demands are perceived as the factors responsible for this de‐coupling phenomenon. However, this notion of decoupling has also met with much skepticism. The detractors would contend that most of the intra‐regional trade is generated by international production fragmentation that drives trading in parts and components. They are then assembled into final products especially in China to be exported extra‐regionally. However, this paper would address the issue of decoupling based not upon trade and production but macroeconomic data as an alternative front.